A rapid literature review on the health-related outcomes of long-term person-centered care models in adults with chronic illness - Cano, Fátima; Alves, Elisabete; João, Ana; Oliveira, Henrique; Pinho, Lara Guedes; Fonseca, César (Frontiers in Public Health, 2023)
Introduction: The strong association between age and the increasing prevalence of chronic diseases, makes it imperative to promote self-care throughout life. Systematic knowledge on the health findings of person-centered care models may contribute to designing effective healthcare strategies to promote empowerment for self-care in long-term care. Objective: To assess the association between the implementation of person-centered care models that promote self-care training in long-term care and health-related outcomes, among adults with chronic illness. Methods: A rapid review of the literature was performed following the Cochrane rapid review methodology. The electronic databases CINAHL, MedicLatina, MEDLINE, and Psychology and Behavioral Sciences Collection were searched for randomized experimental studies, published between 2017 and 2022, that implemented interventions based on person-centered models to promote self-care in adults aged ≥18 years with chronic diseases and needing long-term health care. Verification of the eligibility of the articles and the extraction of data were performed by two independent investigators. Quantitative data on the health-related variables assessed were collected and, through narrative synthesis, health outcomes were grouped into individual, institutional and societal levels. Results: Eight studies, mostly conducted in European countries, were included. All satisfied more than 60% of the methodological quality score. A large variability among studies was found regarding the number of participants, the data collection period and duration of the intervention, the samples selected and the care model implemented. A high number of health-related outcomes (n=17) were analyzed in the studies, using 52 different instruments. The main health-related outcomes were multidimensional, with implications at the individual, institutional and societal levels. The promotion of overall health and wellbeing (n=4), the implementation of patient-centered care models (n=1), the positive and more frequent interactions with health professionals (2), the decrease on staff psychosocial distress (n=1), and the absence of added costs (n=1), while improving family caregivers’ skills (n=1) were the main health-related outcomes described. Conclusions: There is a need to develop robust experimental studies focused on the views and experiences of all stakeholders and conducted in different countries and cultures. Short-, medium- and long-term health outcomes should be measured using internationally accepted and validated scales for chronic patients.